First experience in implantation of a mechanical circulatory support device based on a disk-type pump: an acute experiment - M. O. Zhulkov; A. M. Golovin; E. O. Golovina; A. S. Grenaderov; A. V. Fomichev; S. A. Alsov; A. M. Chernyavsky (Вестник трансплантологии и искусственных органов)
Objective: to carry out the implantation of an artificial left ventricle of the heart based on a disk-type pump in an acute experiment on a large mammal (mini-pig). Materials and methods. To test the surgical technique of implantation and assess the biocompatibility of the apparatus for mechanical support of blood circulation based on a viscous friction pump, an acute experiment was conducted on an animal. A large mammal (mini-pig weighing 90 kg) was used as an experimental model. The implantation of the pump was performed extracorporeally according to the scheme «the apex of the left ventricle – the descending thoracic aorta». During the experiment, invasive blood pressure, central venous pressure, cardiac arrhythmias, body temperature, blood gas composition, activated coagulation time were monitored. Under the control of transesophageal echocardiography, the pump operation mode was set with parameters – speed 2400–2600, productivity 4 ± 0.5 l/min, average IAD – 70–80 mm Hg. Results. In the course of the experiment, the fundamental possibility of using the developed disk-type pump as a device for supporting blood circulation was proved. For 4 hours, the pump provided adequate hemodynamic parameters with an average productivity of 4 ± 0.5 l/min and 2500 rpm. After 4 hours of operation of the pump in the conditions of inactivated heparin (AST – 114 sec), no blood clots were found between the pump disks. Conclusion The hemodynamics feature of the disk pump allows you to develop sufficient performance parameters to ensure adequate blood circulation. The mechanism of action of the «boundary layer» minimizes the risk of blood clots in the pump cavity. However, the topographic and anatomical features of the pig’s body do not allow experiments with a long observation period.